Increased Inflammatory Activity in Patients 3 Months after Myocardial Infarction with Nonobstructive Coronary Arteries. (1st August 2019) - Hjort, Marcus; Eggers, Kai M; Lindhagen, Lars; Agewall, Stefan; Brolin, Elin B; Collste, Olov; Daniel, Maria; Ekenbäck, Christina; Frick, Mats; Henareh, Loghman; Hofman-Bang, Claes; Malmqvist, Karin; et al.
Abstract: BACKGROUND: Around 5%–10% of patients with myocardial infarction (MI) present with nonobstructive coronary arteries (MINOCA). We aimed to assess pathophysiological mechanisms in MINOCA by extensively evaluating cardiovascular biomarkers in the stable phase after an event, comparing MINOCA patients with cardiovascular healthy controls and MI patients with obstructive coronary artery disease (MI-CAD). METHODS: Ninety-one biomarkers were measured with a proximity extension assay 3 months after MI in 97 MINOCA patients, 97 age- and sex-matched MI-CAD patients, and 98 controls. Lasso analyses (penalized logistic regression models) and adjusted multiple linear regression models were used for statistical analyses. RESULTS: In the Lasso analysis (MINOCA vs MI-CAD), 8 biomarkers provided discriminatory value: P-selectin glycoprotein ligand 1, C-X-C motif chemokine 1, TNF-related activation-induced cytokine, and pappalysin-1 (PAPPA) with increasing probabilities of MINOCA, and tissue-type plasminogen activator, B-type natriuretic peptide, myeloperoxidase, and interleukin-1 receptor antagonist protein with increasing probabilities of MI-CAD. Comparing MINOCA vs controls, 7 biomarkers provided discriminatory value: N-terminal pro-B-type natriuretic peptide, renin, NF-κ-B essential modulator, PAPPA, interleukin-6, and soluble urokinase plasminogen activator surface receptor with increasing probabilities of MINOCA, and agouti-related protein with increasing probabilities of controls. Adjusted multiple linear regression analyses showed that group affiliation was associated with the concentrations of 7 of the 8 biomarkers in the comparison MINOCA vs MI-CAD and 5 of the 7 biomarkers in MINOCA vs controls. CONCLUSIONS: Three months after the MI, the biomarker concentrations indicated greater inflammatory activity in MINOCA patients than in both MI-CAD patients and healthy controls, and a varying degree of myocardial dysfunction among the 3 cohorts.